MYB: A Key Transcription Factor in the Hematopoietic System Subject to Many Levels of Control - Lemma, Roza Berhanu; Fuglerud, Bettina Maria; Frampton, Jon; Gabrielsen, Odd Stokke (Advances in experimental medicine and biology, 2024)
MYB is a master regulator and pioneer factor highly expressed in hematopoietic progenitor cells (HPCs) where it contributes to the reprogramming processes operating during hematopoietic development. MYB plays a complex role being involved in several lineages of the hematopoietic system. At the molecular level, the MYB gene is subject to intricate regulation at many levels through several enhancer and promoter elements, through transcriptional elongation control, as well as post-transcriptional regulation. The protein is modulated by post-translational modifications (PTMs) such as SUMOylation restricting the expression of its downstream targets. Together with a range of interaction partners, cooperating transcription factors (TFs) and epigenetic regulators, MYB orchestrates a fine-tuned symphony of genes expressed during various stages of haematopoiesis. At the same time, the complex MYB system is vulnerable, being a target for unbalanced control and cancer development.